The natural product, echinatin, protects mice from methicillin-resistant Staphylococcus aureus pneumonia by inhibition of alpha-hemolysin expression - Zhang, Wei; Gong, Qing; Tang, Zhitong; Ma, Xin; Wang, Zhuoer; Guan, Jiyu; Wang, Li; Zhao, Yicheng; Yan, Ming (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) is a global, multifaceted crisis that poses significant challenges to the successful eradication of devastating pathogens, particularly methicillin-resistant Staphylococcus aureus (MRSA), a persistent superbug that causes devastating infections. The scarcity of new antibacterial drugs is obvious, and antivirulence strategies that reduce the pathogenicity of bacteria by weakening their virulence have become the subject of intense investigation. Alpha-hemolysin (Hla), a cytolytic pore-forming toxin, has a pivotal role in S. aureus pathogenesis. Here, we demonstrated that echinatin, a natural compound isolated from licorice, effectively inhibited the hemolytic activity of MRSA at 32 μg/mL. In addition, echinatin did not interfere with bacterial growth and had no significant cytotoxicity at the inhibitory concentration of S. aureus hemolysis. Heptamer formation tightly correlated with Hla-mediated cell invasion, whereas echinatin did not affect deoxycholic acid-induced oligomerization of Hla. Echinatin affected hemolytic activity through indirect binding to Hla as confirmed by the neutralization assay and cellular thermal shift assay (CETSA). Furthermore, qRT–PCR and western blot analyses revealed that echinatin suppressed Hla expression at both the mRNA and protein levels as well as the transcript levels of Agr quorum-sensing system-related genes. Additionally, when echinatin was added to a coculture system of A549 cells and S. aureus, it significantly reduced cell damage. Importantly, echinatin exhibited a significant therapeutic effect in an MRSA-induced mouse pneumonia model. In conclusion, the present findings demonstrated that echinatin significantly inhibits the hemolysin effect and may be a potential candidate compound for combating drug-resistant MRSA infections.